Impact of thermal radiation on free convection in a differentially heated rolling cubical cabinet - Mikhailenko, Stepan A. (Numerical heat transfer. Part A : Applications)
An interaction of natural convection and surface radiation in a rotating cubic cabinet is scrutinized in this article. The cavity has differentially heated walls, namely opposite heated and cooled walls, while the remaining boundaries are adiabatic. The key equations have been written employing the mass, momentum, and energy conservation laws combined with nonprimitive dimensionless variables including vector potential functions and vorticity vector. The resulting set of equations with the corresponding restrictions has been discretized and resolved employing the finite difference procedure employing a uniform grid. The outcomes have been analyzed for a wide range of key characteristics, including the surface emissivity and the Rayleigh and Taylor numbers. The temperature distributions have been shown during a complete revolution of the chamber. The influence of the governing parameters has been described by changing the mean convective and radiative Nusselt numbers. The results have shown that rotation and radiation can be used as key mechanisms to control the energy transport. Moreover, employing the Boussinesq approach the thermal centrifugal force can be neglected for moderate Rayleigh and Taylor numbers.